The Internet's Negative Impact on the Development of Democracy. - Qianshan, Zhang (Contemporary Chinese Thought)
The Internet has emerged as a product of the information technology revolution with frightening speed. The Internet is a double-edged sword that promotes democracy even as it adversely affects the development of democracy. Its main negative impacts are as follows: the anarchic ultraliberal nature of the network has undermined the normal course of the development of democracy; while the network is becoming increasingly necessary to bring about democracy, one section of the people is being deprived of even more democratic rights; hegemony on the network has intensified the worldwide disequilibrium in the development of democracy; the ease of transmitting information over the network may lead to more covert centralized state rule.